A Finite Element Bendo-Tensegrity Model of Eukaryotic Cell - Bansod, Yogesh Deepak; Matsumoto, Takeo; Nagayama, Kazuaki; Bursa, Jiri (Journal of biomechanical engineering, 2018)
Mechanical interaction of cell with extracellular environment affects its function. The mechanisms by which mechanical stimuli are sensed and transduced into biochemical responses are still not well understood. Considering this, two finite element (FE) bendo-tensegrity models of a cell in different states are proposed with the aim to characterize cell deformation under different mechanical loading conditions: a suspended cell model elucidating the global response of cell in tensile test simulation and an adherent cell model explicating its local response in atomic force microscopy (AFM) indentation simulation. The force-elongation curve obtained from tensile test simulation lies within the range of experimentally obtained characteristics of smooth muscle cells (SMCs) and illustrates a nonlinear increase in reaction force with cell stretching. The force-indentation curves obtained from indentation simulations lie within the range of experimentally obtained curves of embryonic stem cells (ESCs) and exhibit the influence of indentation site on the overall reaction force of cell. Simulation results have demonstrated that actin filaments (AFs) and microtubules (MTs) play a crucial role in the cell stiffness during stretching, whereas actin cortex (AC) along with actin bundles (ABs) and MTs are essential for the cell rigidity during indentation. The proposed models quantify the mechanical contribution of individual cytoskeletal components to cell mechanics and the deformation of nucleus under different mechanical loading conditions. These results can aid in better understanding of structure-function relationships in living cells.
Keywords: Cytoskeleton; biomechanika; analýza metodou konečných prvků; cytoskelet; Actin Cytoskeleton; Finite Element Analysis; Mechanical Phenomena; Microtubules; mikrofilamenta; mechanické jevy; Tensile Strength; Models, Biological; pevnost v tahu; mikrotubuly; biologické modely; eukaryotické buňky; Biomechanical Phenomena; Eukaryotic Cells